Cidadania transcomunicativa: processos comunicacionais de mulheres transexuais e travestis - Luz, Paulo Júnior Melo da (Universidade do Vale do Rio dos Sinos, 2022)
This thesis is constructed in dialogue with transvestites and transsexual women to understand the constitution of their identities and corporalities, in communicational and media processes, in the perspective to build a transcommunicative citizenship. To reach this main goal, are contextualized aspects related to the articulations of transvestite and transsexual women in the organization of social and political movements, the media visibilities and the relations with the Brazilian economic and political scenery; situated the communicational elements that constitute the existences and citizenships of transvestite and transsexual women; reconstituted the communicational trajectories of transvestite and transsexual women and their relations with media to understand how they participate in the construction of their identities and corporalities; and analyzed the experiences and senses from the dialogues with transvestites and transsexual women to elucidate and think about dimensions connected to the construction of transcommunicative citizenship. The research is orientated by the transmethodological perspective, combining theories and methods from different areas in its constructive network. Methodologically, are used bibliographical research, research of the research, theoretical research, contextual research, exploratory and systematic empirical research. The empirical research was built in collaboration with six transvestites and transsexual interlocutors, from different regions in Brazil, with whom were accomplished in-depth semi-structured interviews in Rio Grande do Sul and at Casa Florescer, a shelter for transvestite and transsexual women in São Paulo. To understand the contexts and realities of the interlocutors and from transvestites and transsexual women in Brazil, are problematized the media visibilities of trans people in media, the political representatives in the ambits of the institutional politics, the working of a normative cisgender system and the systemic violence of a necrobiopolitics. The theoretical perspectives include the reflection about cisgender as a social normative pattern, transgender, the gender as central theoretical lens, the self-identifications and self-determinations of gender from transvestite and transsexual women, the feminilities and womanities, the trans coroporalities and identities, and the transcommunicative citizenship. Are analyzed the self-identifications of transvestites and transgender women interlocutors of the thesis and the production of their corporalities; the media experiences and inspirations and the affectation in their corporalities; and the construction of transcommunicative citizenship in six dimensions: philosophical/epistemological; political; popular/from the streets; resistance; hope; and affection.
Keywords: Cidadania transcomunicativa; Transmetodologia; Mulheres transexuais e travestis; Corporalidades; Experiências midiáticas; Transcommunicative citizenship; Transmethodology; Transvestite and transsexual women; Corporalities; Media experiences; ACCNPQ::Ciências Sociais Aplicadas::Comunicação